Health through the Eyes of the Romani minority - Toumová, Kristýna; Tóthová, Valérie; Dušičková, Tereza; Kaas, Jiří; Maňhalová, Jana (Debreceni Egyetemi Kiadó, 2020)
The aim of this study was to ascertain the subjective view of the Romani community on their own health, in the context of social integration and the effects of the environment, using the Transcultural Assessment Model. Methods: The collection of data was conducted via quantitative research using an unstructured questionnaire. The experimental group consisted of 600 members of the Romani minority. Results: The results showed that health is one of the main values that influence the life of the Romani minority. According to a substantial proportion of respondents, they are regularly concerned with matters of their own health; however, most of them do not attend medical check-ups. Conclusion: The concept of sickness and health is highly subjective for each person. Moreover, the culture to which an individual belongs is among the factors that influence an understanding of the concept of health. Thus, when providing medical care, one must also get to know a patient’s culture and their subjective view of health or sickness.
Zdraví očima romské minority
Keywords: Physical fitness; Transcultural Assessment Model; prevention; Romani; mental state; health; Fyzický stav; transkulturní model hodnocení; prevence; Romové; duševní stav; zdraví